2020
DOI: 10.18705/1607-419x-2020-26-3-312-316
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic: the view of a clinical psychologist

Abstract: Recent studies indicate that COVID-19 pandemic has significant negative consequences for the public mental health. These consequences should be assessed and analyzed in the future, but it is already clear, that mass surveys with the use of standard psychological instruments are not adequate for this purpose. The authors emphasize that all stress factors associated with the pandemic (virtual threat and informational stress, deprivation, socioeconomic stress) should be taken into account and qualitatively studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…These findings are consistent with the results of previous studies on the impact of the COVID-19 pandemic on mental health. Both locally in our country and globally, scientists note that the current situation has a serious impact on psychological wellbeing [17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the results of previous studies on the impact of the COVID-19 pandemic on mental health. Both locally in our country and globally, scientists note that the current situation has a serious impact on psychological wellbeing [17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…К факторам, негативно влияющим на процессы личностно-профессионального развития молодежи в целом и студентов, в частности, в последнее время стали добавлять новые источники формирования деструктивного поведения: изменения режима жизнедеятельности, вызванного пандемией. Именно это в последние 2-3 года, по мнению исследователей, стало оказывать сильное влияние на появление новых видов деструктивного поведения у обучающихся (аутодеструктивная и аутоагрессивная формы поведения) [2,[16][17][18]. Еще один деструктивный фактор -распространение экстремистской идеологии, являющейся не только следствием нестабильной социально-политической ситуации в стране, но и результатом ограниченной социальной адаптации молодежи, что требует организации своевременной профилактической работы [19,20].…”
Section: Introductionunclassified
“…An analysis of the researches published during the pandemic showed that already in February 2020, Chinese experts recorded signs of mental distress in 70% of respondents, signs of generalized anxiety disorder in 35.1%, depression in 20.1%, sleep disorders in 18.2% respondents [4]. Failure to cope with stress at the psychological level provide the risk of negative changes in vegetative and humoral regulation and some somatic consequence.…”
Section: Introductionmentioning
confidence: 99%
“…Failure to cope with stress at the psychological level provide the risk of negative changes in vegetative and humoral regulation and some somatic consequence. One of the most common symptom of the stress associated with sleep disturbances [4]. On ICD -10 insomnia define as a sleep disorder associated with difficulties in initiating or maintaining sleep and "a deficiency in the quality and quantity of sleep necessary for normal daytime activities" [5].…”
Section: Introductionmentioning
confidence: 99%